2015
DOI: 10.1039/c5cc00085h
|View full text |Cite
|
Sign up to set email alerts
|

Corynomycolic acid-containing glycolipids signal through the pattern recognition receptor Mincle

Abstract: An enantioselective synthesis of (+)-corynomycolic acid, and its elaboration to esters of trehalose, glucose and glycerol, is described. Trehalose dicorynomycolate and trehalose monocorynomycolate activate human and mouse Mincle as effectively as trehalose dicorynomycolate (cord factor). Glucose monomycolate is revealed to be a potent activator of both mouse and human Mincle. Glycerol monocorynomycolate signals through human Mincle, with the activity predominantly residing in the 2'S-isomer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
63
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(76 citation statements)
references
References 51 publications
(41 reference statements)
2
63
0
Order By: Relevance
“…1 and SI Appendix, Figs. S1-S3), as reported recently (24). Thus, the total number of carbon atoms in the fatty acid did not appear to be the key parameter driving Mincle activity.…”
Section: Deciphering the Structural Features Required For (Glyco)lipidsupporting
confidence: 56%
“…1 and SI Appendix, Figs. S1-S3), as reported recently (24). Thus, the total number of carbon atoms in the fatty acid did not appear to be the key parameter driving Mincle activity.…”
Section: Deciphering the Structural Features Required For (Glyco)lipidsupporting
confidence: 56%
“…A common Mincle ligand signature structure has been predicted based on a number of identified ligands (6,7,(33)(34)(35) in combination with the Mincle protein structure (9)(10)(11)(12). A polar head consisting of glucose or mannose and a hydrophobic chain appear to be the minimum requirement for ligand activity.…”
Section: Discussionmentioning
confidence: 99%
“…As reported in detail previously, the lack of cell wall mycolates in DSM43989 may be due to a deficiency in DIP0789, a putative enoyl coenzyme A (enoyl-CoA) hydratase (Ott et al, submitted). In a recent publication, van der Peet et al reported the chemical synthesis of corynomycolic acids and tested trehalose and glucose mono-and diesters thereof for interactions with human and mouse Mincle using reporter cell lines (34). Notably, not only TDCM but also TMCM, and even glucose monocorynomycolate, triggered Mincle signaling and reporter gene activation.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, not only TDCM but also TMCM, and even glucose monocorynomycolate, triggered Mincle signaling and reporter gene activation. In contrast, when TDB was reduced toward a monosaccharide, namely, glucose behenate, it lost stimulatory activity (34). Similarly, testing of trehalose mono-and diesters of fatty acids of various lengths identified exclusively the diester forms as strong Mincle activators (36).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation